2019
DOI: 10.3847/2041-8213/ab042a
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Interstellar Objects Trapped in the Solar System through Their Orbital Parameters

Abstract: The first interstellar object, 'Oumuamua, was discovered in the Solar System by Pan-STARRS in 2017, allowing for a calibration of the abundance of interstellar objects of its size and an estimation of the subset of objects trapped by the Jupiter-Sun system. Photographing or visiting these trapped objects would allow for learning about the conditions in other planetary systems, saving the need to send interstellar probes. Here, we explore the orbital properties of captured interstellar objects in the Solar Syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…This may indicate that some of them are captives, but it may also, as for short-period comets, reflect an origin in a prograde disc of planetesimals. Note that these results contrast with those of Siraj & Loeb (2019), whose captives are of shorter P, lower e and higher i. Cut-ting our results at their 75th percentile for semi-major axis (a < 16 au) shows that these Centaur-like objects form only 0.2% of the overall captive population, though we do not see the same proclivity for high i in this regime as they do. Figure 2 shows the hyperbolic excess speeds v ∞ of all objects that were consequently captured, which are much lower than the 26 km s −1 of 'Oumuamua or 32 km s −1 of Borisov.…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…This may indicate that some of them are captives, but it may also, as for short-period comets, reflect an origin in a prograde disc of planetesimals. Note that these results contrast with those of Siraj & Loeb (2019), whose captives are of shorter P, lower e and higher i. Cut-ting our results at their 75th percentile for semi-major axis (a < 16 au) shows that these Centaur-like objects form only 0.2% of the overall captive population, though we do not see the same proclivity for high i in this regime as they do. Figure 2 shows the hyperbolic excess speeds v ∞ of all objects that were consequently captured, which are much lower than the 26 km s −1 of 'Oumuamua or 32 km s −1 of Borisov.…”
Section: Resultscontrasting
confidence: 88%
“…Namouni & Morais (2018) suggest that Jupiter's retrograde, co-orbital asteroid has an interstellar origin and was captured 4.5 Gyr ago. Integrating trajectories undergoing a close encounter with Jupiter, Siraj & Loeb (2019) found that objects captured in this way may have orbits similar to those of the 'Centaurs' with inclination i > 48 • and concluded that those may be captured ISOs. Grishin et al (2019) demonstrated that interstellar objects may be captured as a result of interactions with a primordial protoplanetary gas disc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to 'Oumuamua, CNEOS 2014-01-08 (Siraj & Loeb 2019a) was tentatively the first interstellar meteor discovered larger than dust, and 2I/Borisov (Guzik et al 2019) was the first confirmed interstellar comet.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of an interstellar comet cloud could partly explain the slightly hyperbolic comets and potential interstellar objects that might have been detected in the solar system but not yet classified as such (see e.g. Ashton et al 2018;Siraj & Loeb 2019). A future detailed study of the evolution of the TICs created by the tides and stellar encounters is needed to draw more solid conclusions.…”
Section: Galactic Tide and Gaia Star Perturbationmentioning
confidence: 99%